Application of the boundary element method for heat distribution on ferromagnetic core - (:unkn) unknown (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2008)
This paper presents analysis of the electro-thermal transformation problem and its effect on a ferromagnetic core. The two-dimensional heat conduction problem is studied using the boundary element method (BEM). Linear elements are used in the solution procedure. The numerical results have been compared with the results of the finite element method (FEM). Three different widely - used ferromagnetic materials have been examined in the analysis.
Keywords: boundary element method; ferromagnetic materials; thermal analysis; actuator